Shaping professional identity across borders: Indonesian pre-service EFL teachers in Philippine classroom - Arilia Triyoga; Ikmi Nur Oktavianti; Muhamad Argi Afriandi (Englisia: Journal of Language, Education, and Humanities, 2026)
The professional identity of prospective English teachers plays a pivotal role in enhancing the quality of educators in Indonesia, which in turn exerts a significant influence on the nation's overall educational outcomes. This study aims to (1) explore the teaching experiences of prospective English teachers from Muhammadiyah universities (EFL pre-service teachers) during their teaching practicum in the Philippines, and (2) describe how this transnational teaching experience contributes to the development and transformation of their professional identity. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, document analysis (including teaching practicum reports and reflective journals), and reflection journal entries maintained throughout the program. Participants were Muhammadiyah University students who completed a one-month teaching practicum in schools in the Philippines. Data analysis was conducted using thematic techniques, guided by the theoretical framework of teacher professional identity, enabling the mapping of students' experiences into key themes relevant to identity formation. The findings reveal that pre-service teachers encountered linguistic and cultural differences, novel pedagogical practices, pedagogical challenges accompanied by coping strategies, as well as emotional and professional adjustments during the SEA-Teacher program in the Philippines. Furthermore, this transnational exposure contributed to their professional identity development through shifts in their perception of the teaching profession, enhanced pedagogical confidence, and identity negotiation within a global context.